Bone Mineral Densitometry as Suggested Initial Test for Spina Bifida Patient to Prevent Minimal Trauma Fracture: A Literature Review and Case Report - Victor Kurniawan Chandra; Jeffrey Jonathan Tedjajuwana (Universitas Malahayati, 2026)
ABSTRACT Bone fracture occurs when a force exerted against a bone is stronger than the bone can bear. This leads to pain, loss of function and sometimes bleeding and injury around the site. Spina bifida is a condition that affects the spine and is usually apparent at birth. It is a type of neural tube defect. This young spina bifida patient present with bone fracture. The patient does not have sufficient information and evaluation related to prevent spina bifida complications. A 24 years old spina bifida patient came to emergency department feeling pain at right shoulder and upper right arm since a week before admission. He had history of lifting his nephew and moving a water gallon. Swelling was revealed on the medial and lateral sides of the right upper arm, minimal deformity with hematoma, and no open wound. X-ray of the right shoulder showed fracture of the right humeral neck. Then the surgeon performed close reduction without internal fixation and immobilized the humeral. The result obtained from this procedure was satisfying and the arm could function properly. The common cause of bone fracture are trauma, osteoporosis, and overuse. Minimal trauma fracture is fracture that occur following little or no trauma and related to osteoporosis. Patients with spina bifida are at increased risk for fractures and low bone mass density. Bone mineral density have an important role in the evaluation of individuals at risk of osteoporosis, and in helping clinicians advise patients about the appropriate use of antifracture treatment. Bone mass densitometry or dual energy x-ray absorptiometry is considered useful and reliable to check bone density. This tool can be suggested as an initial screening test especially in spina bifida patient to prevent future osteoporosis and minimal trauma fracture as undesirable complications. Keywords: Bone Mineral Densitometry, Minimal Trauma, Spina Bifida, Suggested Initial Test.